2009
DOI: 10.4067/s0717-92002009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la inoculación con microorganismos fijadores de nitrógeno asimbióticos aislados de la rizósfera de Pinus patula en Colombia

Abstract: SUMMARYThe effects on different vegetal parameters of asymbiotic nitrogen-fixing bacteria isolated from the rhizosphere of Pinus patula were studied under greenhouse conditions, in experiments designed for statistical analysis using these forest specie seedlings. This research also examined the interactions of ectomycorrhizal fungus Suillus luteus and the microorganism isolates in P. patula, as well as the nitrogenase activity in these bacteria by acetylene reduction assay. The free nitrogen-fixing bacteria Az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
3
1
2
Order By: Relevance
“…Plant height (cm) Shoot dry weight (g) Root collar diameter (mm) Ectomycorrhizal colonization (%) 3.9 (0.7) 0.7 (0.1) 1. dependent on root ectomycorrhizal colonization, as reported for species such as P. pinaster [8], P. pinea [21], and P. thunbergii [22], and the values for ectomycorrhizal colonization are comparable with those reported [19,20]. The differences in root ectomycorrhizal colonization levels seem to be in turn determined by the EPD level of the inocula tested (ES inoculum = 34 per g and EM inoculum = 156 per g).…”
Section: Inoculum Dilutionsupporting
confidence: 79%
See 1 more Smart Citation
“…Plant height (cm) Shoot dry weight (g) Root collar diameter (mm) Ectomycorrhizal colonization (%) 3.9 (0.7) 0.7 (0.1) 1. dependent on root ectomycorrhizal colonization, as reported for species such as P. pinaster [8], P. pinea [21], and P. thunbergii [22], and the values for ectomycorrhizal colonization are comparable with those reported [19,20]. The differences in root ectomycorrhizal colonization levels seem to be in turn determined by the EPD level of the inocula tested (ES inoculum = 34 per g and EM inoculum = 156 per g).…”
Section: Inoculum Dilutionsupporting
confidence: 79%
“…The results clearly demonstrated that both factors inoculum type and dilution level had significant effects on P. patula seedling growth. The treatments with undiluted inocula were most effective for promoting seedling growth; nevertheless, the most significant growth was still lower than that reported for other species (P. maximinoii, P. oocarpa, and P. tecunumanii) [19,20].…”
Section: Discussioncontrasting
confidence: 59%
“…Surprisingly, in P. patula the foliar P concentration was not signi cantly a ected by dose and inoculum type, whereas in P. maximinoi there were interactive e ects. is may be due to a dilution e ect that masked the increase in seedling P uptake or intrinsic di erences in growth rates between both species [4,41,42]. Note that P. maximinoi exhibited higher growth values than P. patula, which perhaps limited the plant P uptake in the latter.…”
Section: Implications For Practicementioning
confidence: 98%
“…In the case of non-leguminous plants, there is no symbiotic relation, therefore the plant is inoculate with free-living N2 fixing bacteria, such as Azotobacter and Azospirillium. These were inoculated in patula pine (Orozco & Martínez, 2009), pastures (Garrido et al 2010, Cárdenas et al 2010, Cárdenas et al 2014), stevia (Borda et al 2011), vegetables (Jiménez et al 2011, eucalyptus (Obando et al 2010, Rojas et al 2013, and maize (Rojas et al 2012). In high efficiency plants having photosynthesis (C4 plants) sugar cane and corn, successful results have been obtained when inoculated into the rhizosphere.…”
Section: Analysis Of Co-occurrencementioning
confidence: 99%